Pengaruh Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai pada Dinas Pendidikan Pemuda dan Pelatihan Olahraga Kabupaten Karawang - Anisa Nurlaela Sari; Suroso; Flora Patricia Anggela (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study was conducted with the aim of knowing the partial and simultaneous influence between work discipline and work environment on the performance of employees of the Karawang Regency Youth Education and Sports Office. The method used in this research is quantitative method. The study population consisted of 80 employees of the Karawang Regency Youth Education and Sports Office, using a saturated sample sampling technique, where the entire population became the research sample. Data analysis was carried out using the Validity Test, Reliability Test, Normality Test, and Hypothesis Test using the t Test (Partial) and F Test (Simultaneous). The results of this study indicate that there is a partial influence between work discipline and the work environment of the Service with a t table value (7.386> 1.991). There is also a partial influence between the work environment and employee performance with a t table value (2.629> 1991). In addition, the level of employee performance is jointly influenced by work discipline and work environment. This can be seen from the calculated F value (59.873> 2.72.) The magnitude of the influence of work discipline and work environment on employee performance at the Youth and Sports Education Office is 60.9%.